Redes de confianza online y flash mobs: movilizados por la educación - Ponce Lara, Camila; Miranda, Natalia (Observatorio (OBS*), 2016)
The largest Chilean student movement after the return of democracy emerged during 2011, with structural demands about the educational system, such as an end to profit in education, and free education of quality. A key element of the reach of the students was the intensive use of online platforms as a means of organization, dissemination, and debate. Therefore, the objective of this study is to analize the “online trust networks” Tilly’s concept penetrated by procedures of the online society and the use of the internet, focusing on a particular form of collective action, that of flash mobs. The methodology used is qualitative analysis, using semi-structured interviews and focus groups with the leaders and organizers of the flash mobs, as well as leaders of the student movement in general. As a result of this exploratory research, ῝online trust networks῞ configured from online platforms that make it possible to link unknown individuals together around a common goal are observed. These specific ῝online trust networks῞ of the flash mobs arise quickly, with strong ties for their execution but weak in their permanence and dissolution.